2021
DOI: 10.1016/j.amsu.2021.102459
|View full text |Cite
|
Sign up to set email alerts
|

IN-SILICO dynamic analysis of Sulawesi propolis as anti-endometriosis drug: Interaction study with TNF alpha receptor, NF-kB, estrogen receptor, progesterone receptor and prostaglandin receptor

Abstract: Introduction Endometriosis is a disease that impacts around 10% of all women in reproductive age, with pelvic pain and infertility as its main clinical features. Current medical treatment targeting lowering estrogen activity has not shown sufficient result due its side effects and reproductive function suppression. Propolis has been widely studied, showing anti inflammation and pro-apoptosis property, that could potentially be used in the treatment of endometriosis. This study investigates the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
(17 reference statements)
1
5
0
1
Order By: Relevance
“…Another study with peritoneal fluid from women with endometriosis showed that TNFA signaling can increase EGR1 expression and collaborate with the establishment and maintenance of the disease [71]. In addition, TNFA can be increased by NFkB accelerating the prolonged inflammatory process responsible for the reduction of apoptosis activity in endometriosis [72], making sense for TNFA signaling via the NFkB pathway in our findings.…”
Section: Discussionsupporting
confidence: 62%
“…Another study with peritoneal fluid from women with endometriosis showed that TNFA signaling can increase EGR1 expression and collaborate with the establishment and maintenance of the disease [71]. In addition, TNFA can be increased by NFkB accelerating the prolonged inflammatory process responsible for the reduction of apoptosis activity in endometriosis [72], making sense for TNFA signaling via the NFkB pathway in our findings.…”
Section: Discussionsupporting
confidence: 62%
“…Another study with peritoneal fluid from women with endometriosis showed that TNFA signaling could increase EGR1 expression and collaborate with establishing and maintaining the disease [ 76 ]. In addition, TNFA can be increased by NFkB, accelerating the prolonged inflammatory process responsible for the reduction of apoptosis activity in the disease [ 77 ], making sense for TNFA signaling via the NFkB pathway in our findings.…”
Section: Discussionmentioning
confidence: 69%
“…Our findings highlight primary changes in the endometriosis MenSCs that may favor the tissue implantation at the ectopic site. The global expression profile enriched critical pathways already related to the endometriosis condition, such as PI3K signaling via AKT to mTORC1 [ 63 , 64 , 65 ], mTORC1 signaling [ 97 ], TNFA signaling via NFkB [ 76 , 77 ], IL6 STAT3 signaling [ 75 ], TGF beta signaling [ 72 , 73 ], and hypoxia via HIF1A targets [ 74 ]. These dysregulations suggest that the chronic inflammatory endometrial microenvironment [ 26 ] can modulate these cells and provide opportunities for the etiopathogenesis of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Çalışma sonucunda propolis, endometriyozis ile ilgili reseptörlere karşı güçlü bir bağlanma potansiyeli göstermesine rağmen, gerçek biyolojik bir etki gösterememiştir. Çalışmada propolisin endometriyozis dokusu üzerindeki etkili dozunu saptamak amacıyla farklı klinik deneysel çalışmalara ihtiyaç olduğu vurgulanmıştır (55).…”
Section: Rahimjanova Vd: Apiterapiunclassified